FLORA OF ACARLAR LONGOZ (FLOODPLAIN) (SAKARYA) AND ITS SURROUNDINGS - Didem Karaduman; Mehmet Sağıroğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, one of the Turkey's Wetlands of International Importance Grounds, declared as Wildlife Protection Area and Grade 1 Natural Protected Area called Acar Longoz (Sakarya) and its surroundings’ floristic features were studied. The study area is on the A3 square according to Davis's Grid Frame System. As a result of the studies carried out in the Acarlar floodplain, there were 360 genera, 654 species and subspecies taxa belonging to 97 families. Of the taxa identified in the area, 8 belong to Pteridophyta, 646 to Spermatophyta, 5 of which belong to Gymnospermae and 641 to Angiospermae subdivision. The endemism rate of the area was determined to be 2,137 % with 14 taxa. The number of taxa belonging to the European-Siberian phytogeographical region is in the first place with 21.47%. Additional information was also given about the remarkable plants in the research area.